Tunable Supramolecular Chirogenesis in the Self-Assembling of Amphiphilic Porphyrin Triggered by Chiral Amines - Savioli, Marco (Int J Mol Sci, 2020)
Supramolecular chirality is one of the most important issues in different branches of science and technology, as stereoselective molecular recognition, catalysis, and sensors. In this paper, we report on the self-assembly of amphiphilic porphyrin derivatives possessing a chiral information on the periphery of the macrocycle (i.e., D- or L-proline moieties), in the presence of chiral amines as co-solute, such as chiral benzylamine derivatives. The aggregation process, steered by hydrophobic effect, has been studied in aqueous solvent mixtures by combined spectroscopic and topographic techniques. The results obtained pointed out a dramatic effect of these ligands on the morphology and on the supramolecular chirality of the final self-assembled structures. Scanning electron microscopy topography, as well as fluorescence microscopy studies revealed the formation of rod-like structures of micrometric size, different from the fractal structures formerly observed when the self-assembly process is carried out in the absence of chiral amine co-solutes. On the other hand, comparative experiments with an achiral porphyrin analogue strongly suggested that the presence of the prolinate moiety is mandatory for the achievement of the observed highly organized suprastructures. The results obtained would be of importance for unraveling the intimate mechanisms operating in the selection of the homochirality, and for the preparation of sensitive materials for the detection of chiral analytes, with tunable stereoselectivity and morphology.